2020
DOI: 10.1002/smll.202001573
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Piezophoto Coupling Catalysis Behavior of BiOX/BaTiO3 (X = Cl, Br, Cl0.166Br0.834) Piezoelectric Composites

Abstract: Polarization field engineering of piezoelectric materials is considered as an advisable strategy in fine‐tuning photocatalytic performance which has drawn much attention recently. However, the efficient charge separation that determines the photocatalytic reactivities of these materials is quite restricted. Herein, a judicious combination of piezoelectric and photocatalytic performances of BiOX/BaTiO3 (X = Cl, Br, Cl0.166Br0.834) to enable a high piezophotocatalytic activity is demonstrated. Under the synergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(53 citation statements)
references
References 59 publications
2
51
0
Order By: Relevance
“…These positive and negative charges will transfer to the opposite directions under the influence of the alternating built-in electric field. In the condition of both light and ultrasound, the electrons and holes located at the conductive band and valance band will transfer to the opposite directions under the internal piezoelectric potential, causing electrons to accumulate in the conductive band of BiOCl and holes accumulate in the valance band of NaNbO 3 [ 32 , 33 , 34 ]. Subsequently, the electrons on the CB of BiOCl combined with the absorbed O 2 to produce ·O 2 − .…”
Section: Resultsmentioning
confidence: 99%
“…These positive and negative charges will transfer to the opposite directions under the influence of the alternating built-in electric field. In the condition of both light and ultrasound, the electrons and holes located at the conductive band and valance band will transfer to the opposite directions under the internal piezoelectric potential, causing electrons to accumulate in the conductive band of BiOCl and holes accumulate in the valance band of NaNbO 3 [ 32 , 33 , 34 ]. Subsequently, the electrons on the CB of BiOCl combined with the absorbed O 2 to produce ·O 2 − .…”
Section: Resultsmentioning
confidence: 99%
“…Bai et al reported that the introduction of oxygen vacancy into ZnO can increase the concentration of free electrons and hence enhances the piezocatalytic activity in dyes degradation [20] . Zhou et al loaded BiOX (X = Cl, Br, and Cl 0.166 Br 0.834 ) on BaTiO 3 surface [21] . The formed heterojunction structure extends the lifetime of free charge carriers and hence elevates the piezocatalytic activity of BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the BT-based perovskite structure has excellent piezoelectric, ferroelectric, and dielectric properties, and the preparation process is compatible with the traditional lead-based ceramic process. Hence, this has become the most widely investigated structure with the best development potential in recent years [ 52 , 53 ]. Current research mainly considers three aspects for improving the piezoelectric performance of lead-free piezoelectric ceramics.…”
Section: Principle and Process Of Pe And Tengmentioning
confidence: 99%